MEMBANGUN MANAJEMEN PENGETAHUAN DALAM KETAHANAN PANGAN - Muhammad Ilyas Sikki (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2010)
Knowledge is a commodity or intellectual assets. Knowledge have characteristics such as, use of knowledge will not spend, transfer of knowledge will not eliminate, the amount of knowledge is abundant but has limited in use and a lot of knowledge just disappear. Two important categories of knowledge that is tacit knowledge andexplicit knowledge. Knowledge management is the process of capturing (capturing knowledge), find or create (discovery knowledge), sharing and transfer, and apply knowledge to encourage the innovation process. Knowledge management is a multidisciplinary field that covers a lot of things. While the knowledge management system is a virtual storage of relevant information critical to daily tasks in a company or organization. Knowledge management take a systematic approach in the use of information to supply flow of knowledge for decision making efficient and effective. Knowledge Management in charge of ensuring that both categories of knowledge (explicit and tacit) can be maintained, developed and applied to the progress of an organization or company. Therefore, knowledge management has become crucialfor the development offood security in Indonesia for the community active and healthy individuals